Pengaruh Tingkat Hutang dan Inventory Intensity terhadap Manajemen Pajak - Astuti, Reni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
This research aims to investigate the impact of Debt Levels and Inventory Intensity on Tax Management Practices in Manufacturing Companies listed on the Indonesia Stock Exchange during the 2017-2021 period. A quantitative approach was used by collecting secondary data from the financial reports of 177 companies. The sample consisted of 54 manufacturing companies selected purposively, with a total of 230 data analyzed. Analysis was carried out using descriptive statistics, classical assumption tests, and panel data regression using Eviews version 12 software. The results showed that there was no significant influence between Debt Level (X1) and Inventory Intensity (X2) on Tax Management Practices (Y). These findings highlight the possibility of other factors having a more dominant role in tax management practices in the context of this research.